2003
DOI: 10.1002/hlca.200390091
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of N1‐Hydroxylophine N3‐Oxide (=1‐Hydroxy‐2,4,5‐ triphenyl‐1H‐imidazole 3‐Oxide) in the Solid State

Abstract: Dedicated to Professor Jack D. Dunitz on the occasion of his 80th birthdayThe crystal structure of 1-hydroxy-2,4,5-triphenyl-1H-imidazole 3-oxide (1) has been determined from laboratory X-ray powder-diffraction data. The two independent molecules in the asymmetric unit form chains via OÀH ¥¥¥ O hydrogen bonds related by a twofold screw axis. One of the O ¥¥¥ O distances is extremely short (2.32(1) and 2.43(1) ä). Solid-state NMR spectroscopy (CPMAS) combined with calculation of absolute shieldings (GIAO/B3LYP/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Further, 1-hydroxy-2,4,5-triphenyl-1H-imidazole 3-oxide, a molecule with the potential for intermolecular proton transfer in the solid state, has been under intensive study [144]. X-ray powder diffraction data revealed that the two independent molecules in the asymmetric unit form chains via O-H…O hydrogen bonds related by a twofold screw axis.…”
Section: Hydrogen Bonding and Prototropic Tautomerismmentioning
confidence: 99%
“…Further, 1-hydroxy-2,4,5-triphenyl-1H-imidazole 3-oxide, a molecule with the potential for intermolecular proton transfer in the solid state, has been under intensive study [144]. X-ray powder diffraction data revealed that the two independent molecules in the asymmetric unit form chains via O-H…O hydrogen bonds related by a twofold screw axis.…”
Section: Hydrogen Bonding and Prototropic Tautomerismmentioning
confidence: 99%
“…6 In 15 N-NMR, solid ammonium chloride was used as reference and the chemical shift data were transformed to external nitromethane through the equation: δ (NO 2 CH 3 ) = δ(NH 4 Cl) -338.1 ppm. 7 When analyzing the NMR parameters reported in Table 1 for 1 H-NMR, In solution, the 13 C-NMR data for C-3 and C-5 of HPz-(1) cannot be compared with those of the corresponding complexes because a mean value of 148.5 ppm, corresponding to the two degenerate forms a and b in fast exchange equilibrium, is observed at 300 K. 8 The coordination Although to a lesser extent, a similar effect takes place on C-ortho.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous paper we determined the structure of N 1 -hydroxylophine N 3 -oxide (or 1-hydroxy-2,4,5-triphenyl-1H-imidazole 3-oxide) 1 from X-ray powder diffraction data [1]. The two independent molecules in the asymmetric unit form chains by O H· · ·O hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%